Effectiveness and safety of blonanserin for improving social and cognitive functions in patients with first-episode schizophrenia: a study protocol for a prospective, multicentre, single-arm clinical trial. Issue 4 (20th April 2022) - Pu, Chengcheng; Lei, Lei; Yang, Fude; Deng, Hong; Sheng, Jianhua; Liu, Zhening; Hu, Shaohua; Wang, Lina; Wu, Bin; Bo, Qijing; Inoue, Yoshifumi; Yu, Xin
Abstract : Introduction: Both the pharmacological characteristics of blonanserin and its related small sample size studies suggest that blonanserin could alleviate social and cognitive dysfunctions in patients with schizophrenia. However, no large sample size studies have been performed so far. This study aimed to investigate the effectiveness and safety of blonanserin in improving social and cognitive functions in patients with first-episode schizophrenia. Methods and analysis: This is a prospective, multicentre, single-arm clinical trial. A total of 188 patients with first-episode schizophrenia will be enrolled and will undergo a 0–7 day washout period before blonanserin administration. Doses of blonanserin will first be set to 4 mg P.O. twice per day after meals and gradually increased to 8–16 mg/d P.O., depending on patient's age and symptoms, for 26 weeks. Maximum dose of blonanserin will not be exceeding 24 mg/day. The primary endpoint of the study is the changes of Personal and Social Performance (PSP) score in patients from baseline to week 26. Secondary endpoints include changes in MATRICS consensus cognitive battery (MCCB), Paced Auditory Serial Addition Test (PASAT), grooved pegboard test (GPT), Positive and Negative Syndrome Scale (PANSS) total score and PANSS 5-factor subscale scores. Other endpoints include changes of serum brain-derived neurotrophic factor (BDNF) at corresponding visits and MRI results. Moreover, incidence of adverse events, changes in endocrine and metabolic profiles, renal, hepatic and sexual functions and extrapyramidal symptoms will be strictly monitored and recorded. Ethics and dissemination: The study was approved by the ethics committee of the leading site Peking University Sixth Hospital (No. 2018–18), and all included patients are requested to provide written informed consent before enrolment. The study will be conducted according to the principles of the Declaration of Helsinki and follow the principles for clinical research. Trial registration number: NCT03784222 .